The development of basketball players: current perspectives and future directions - Branquinho, Daniel; Ferraz, Ricardo; Marinho, Daniel A; Neiva, Henrique P.; Teixeira, José E; Forte, Pedro; Marques, Mário C; Branquinho, Luís (Open Science Journal, 2022)
The identification and development of talent in basketball has been seen as a dynamic and complex process. Furthermore, there are numerous factors that play an important role in the evolution of the basketball player during childhood and adolescence. In this brief review, we critically analyze the main factors to be considered in the development of young basketball players. Furthermore, it focuses on the importance of key variables considered in the talent detection process and in long-term development programs. It can be concluded that the maturational status of young basketball players should be considered in the formulation of test batteries for talent detection and in long-term development programs to ensure that potential talents are not excluded due to late maturation in relation to their pairs.